Synthesis and properties of eco-friendly novolac phenolic resin from liquefied coir husk / Nor Mazlina Abdul Wahab … [et al.] - Abdul Wahab, Nor Mazlina; Samsudin, Dalina; Majid, Noor Aishatun; Mohd Ishak, Mohd Azlan Mohd Ishak; Daik, Rusli (Research Management Institute, 2016)
Phenolic resin is thermoset plastics that had been widely used in various applications such as the production of furniture, insulation, friction, coating and moulding. Phenolic resin is conventionally produced by reaction of phenol and formaldehyde whereby phenol was synthesized from petroleum source. Due to depleting of petroleum as the main source of raw materials, thus alternative choices should be taken to overcome the crucial problem. The use of natural biomass fiber such as wood or coconut coir husk is considered the best candidates so far. The coconut coir husk (CCH) was chosen as raw material due to its relatively high composition of lignin (59%) thermal stability and abundantly available biomass in Arau, Perlis and most of states in Malaysia. Lignin has a similar structure to phenol and considered as a phenolic material. Studies on synthesizing phenolic resin from liquefied wood had been done extensively elsewhere. However there are so limited literatures were found for CCH. Therefore, in this study, liquefied CCH will be used as feed stocks in condensation reaction to produce Novolac Phenolic resin. The liquefied CCH phenolic resin will be characterized and the mechanical properties will be investigated. Thus, the objectives of this study involve characterizing the properties of resin produce using gel permeation chromatography (GPC), Fourier Transform - Infra-Red (FT-IR) and High Performance Liquid Chromatography (HPLC). The resin produced also will be evaluated on their physical and mechanical properties using flexural tensile test. The significant outcomes of this study will benefit the environment by reducing the uses of synthetic phenol and eco-friendly Novolac Phenolic resin will be synthesized.